Perspectives and challenges of epigenetic determinants of childhood obesity: A systematic review. (23rd November 2021) - Alfano, Rossella; Robinson, Oliver; Handakas, Evangelos; Nawrot, Tim S.; Vineis, Paolo; Plusquin, Michelle
Summary: The tremendous increase in childhood obesity prevalence over the last few decades cannot merely be explained by genetics and evolutionary changes in the genome, implying that gene–environment interactions, such as epigenetic modifications, likely play a major role. This systematic review aims to summarize the evidence of the association between epigenetics and childhood obesity. A literature search was performed via PubMed and Scopus engines using a combination of terms related to epigenetics and pediatric obesity. Articles studying the association between epigenetic mechanisms (including DNA methylation and hydroxymethylation, non‐coding RNAs, and chromatin and histones modification) and obesity and/or overweight (or any related anthropometric parameters) in children (0–18 years) were included. The risk of bias was assessed with a modified Newcastle–Ottawa scale for non‐randomized studies. One hundred twenty‐one studies explored epigenetic changes related to childhood obesity. DNA methylation was the most widely investigated mechanism ( N = 101 studies), followed by non‐coding RNAs ( N = 19 studies) with evidence suggestive of an association with childhood obesity for DNA methylation of specific genes and microRNAs (miRNAs). One study, focusing on histones modification, was identified. Heterogeneity of findings may have hindered more insights into the epigenetic changes related to childhood obesity. Gaps and challenges that future research should face are herein described.